Evidence accumulation in the pre-supplementary motor area and insula drives confidence and changes of mind - Dorian Goueytes; François Stockart; Alexis Robin; Lucien Gyger; Martin Rouy; Dominique Hoffmann; Lorella Minotti; Philippe Kahane; Michael Pereira; Nathan Faivre (Nature Communications)
Abstract Evidence accumulation is a powerful mechanism to explain the temporal dynamics of decisions, as well as their metacognitive components such as confidence judgments and changes of mind. However, it is still unclear how and where in the brain evidence accumulation leads to these two metacognitive components. We report intracranial high-gamma activity in patients with epilepsy recorded while they perform a visual discrimination task and estimate their confidence level. Our results indicate an anatomical overlap between the neural correlates of evidence accumulation, confidence, and changes of mind in the pre-supplementary motor area, as well as in the orbitofrontal, inferior frontal, and insular cortices. Behavioural and electrophysiological results are reproduced with a post-decisional evidence accumulation model, and the temporal dynamics of decision-making is characterized with mouse-tracking and intracranial electrophysiology. We conclude that confidence and changes of mind result from evidence accumulation, instantiated before the decision in the pre-supplementary motor area, and after the decision in the insula.